Insight Into the Current Directions in Functionalized Nanocomposite Hydrogels - Esmaeely Neisiany, Rasoul; Enayati, Mohammad Saeid; Sajkiewicz, Paweł; Pahlevanneshan, Zari; Ramakrishna, Seeram (Frontiers in Materials, 2020)
Since the introduction of tissue engineering as an encouraging method for the repair and regeneration of injured tissue, there have been many attempts by researchers to construct bio-mimetic scaffolds which mimic the native extracellular matrix, with the aim of promoting cell growth, cell proliferation, and restoration of the tissue’s native functionality. Among the different materials and methods of scaffold fabrication, one particularly promising class of materials, hydrogels, has been extensively studied, with the inclusion of nano-scaled materials into hydrogels leading to the creation of an exciting new generation of nanocomposites, known as nanocomposite hydrogels. To closely mimic the native tissue behavior, scientists have recently focused on the functionalization of incorporated nanomaterials via chiral biomolecules, with reported results showing great potential. The current article aims to introduce a perspective of nano-scaled cellulose as a promising nanomaterial which can be multi-functionalized for the fabrication of nanocomposite hydrogels with applications in tissue engineering and drug delivery systems. This article also briefly reviews the recently reported literature on nanocomposite hydrogels incorporated with chiral functionalized nanomaterials. Such knowledge paves the path for the development of tailored hydrogels toward practical applications.